Glycerol-enriched heterogeneous catalyst for biodiesel production from soybean oil and waste frying oil - Gabriel O. Ferrero (2015)
In the present work, biodiesel production using a glycerol enriched heterogeneous catalyst was studied. For that purpose, the catalyst performance at different glycerol concentrations and reaction conditions (under ambient atmosphere) was evaluated and two triglyceride sources were used. The most active catalyst was produced using CaO, glycerol and methanol at a mass ratio of 1:1.6:13.4, respectively. By performing the transesterification reaction under ambient atmosphere during 2 h at 333 K, using 0.4 wt.% of catalyst and 7:1 methanol to oil molar ratio, a good quality product was obtained (EN 14214) using both soybean oil and waste frying oil. The catalyst could be re-used during four cycles and could also be prepared by using ethanol instead of methanol (with differences <4% on product conversion). The glycerol by-product, being rich in calcium soaps, might additionally be used for the enrichment of animal diets. The present process allowed the production of biodiesel from different triglyceride sources using a very active heterogeneous catalyst at competitive reaction conditions compared to the homogeneous process and also enabled a two-way recycling of the glycerol by-product.